The influence of Islamic philosophy in the formation of traditional housing in Bukhara - Fayzullaeva, Н.Н. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2022)
This work is based on the findings of a scientific work that is devoted to the methods of regeneration of traditional housing (the end of the XIX and the beginning of the XX century) of the old city part of the city of Bukhara. The author quotes fragments of Qur'an and hadis (stories from the life of the prophet Muhammad s.a.s.) which are canons for the Islamic world and that influenced the formation of planning, spatial composition, decor and even construction details of historic dwellings in Bukhara. As a result of this work, the author lists the developed methods for the restoration and regeneration of historical houses in the city of Bukhara. The article also discusses the principles of preservation and restoration of historical cities. The author gives his principle of restoration - this is to be based on the canons of Muslim culture. And this is the novelty of this work in this area.